A 4000-year debris flow record based on amphibious investigations of fan delta activity in Plansee (Austria, Eastern Alps) - Kiefer, Carolin; Oswald, Patrick; Moernaut, Jasper; Fabbri, Stefano Claudio; Mayr, Christoph; Strasser, Michael; Krautblatter, Michael (Earth Surface Dynamics, 2021)
The frequency of debris flows is hypothesized to have increased in recent decades with enhanced rainstorm activity. Geological evidence to test the relationship between climate and debris flow activity for prehistoric times is scarce due to incomplete sediment records, complex stratigraphy, and insufficient age control, especially in Alpine environments. In lacustrine archives, the link between onshore debris flow processes and the sedimentary record in lakes is poorly investigated. We present an amphibious characterization of alluvial fan deltas and a continuous 4000-year debris flow record from Plansee (Tyrol, Austria), combining light detection and ranging (lidar) data, swath bathymetry, and sediment core analyses. The geomorphic investigation of two fan deltas in different developmental stages revealed an evolutionary pattern of backfilling and new channel formation onshore, together with active subaqueous progradation on a juvenile fan delta, major onshore sediment deposition, and only few, but larger, subaqueous deposits on a mature fan delta. Geomorphic evidence for stacked and braided debris flow lobes, subaquatic landslide deposits, and different types of turbidites in sediment cores facilitated a process-based event identification, i.e. distinguishing between debris-flow-induced or earthquake-induced turbidites throughout the 4000-year sedimentary record. We directly correlate subaqueous lobe-shaped deposits with high backscatter signals to terrestrial debris flow activity of the last century. Moreover, turbidite thickness distribution along a transect of four cores allows us to pinpoint numerous events as being related to debris flow activity on a juvenile fan delta. In the sediment core, debris-flow-induced turbidites feature a more gradual fining upward grain size trend and higher TOC (total organic carbon) and delta C-13 values compared to earthquake-induced turbidites. The 4000-year event record contains 138 debris-flow-induced turbidites separated into four phases of similar debris flow activity (df phases). df phase 1 (similar to 2120 to similar to 2040 before the common era - BCE) reflects the second-highest observed event frequencies and is interpreted as being a postseismic landscape response. After a long period of long recurrence intervals without any outstanding increases in debris flow activity during df phase 2 (similar to 2040 BCE to similar to 1520 common era - CE), there are slightly increased event frequencies in df phase 3 (similar to 1520 to similar to 1920 CE). df phase 4 (similar to 1920 to 2018 CE) exhibits a drastic increase in debris flow activity, followed by the overall highest debris flow frequency of the whole record, which is about 7 times higher than during df phase 3. We show that the frequency increase in the debris-flow-induced turbidite record matches a previously postulated increase in debris flow events derived from aerial photography at Plansee in the last century. The triggering of debris flows is more controlled by short, intense precipitation than any other mass movement process, and we demonstrate that lacustrine debris flow records provide a unique inventory of hazard-relevant rainstorm frequencies over decades, centuries, and millennia. The presented increase in debris flow frequency since the start of the 20th century coincides with a twofold enhanced rainstorm activity in the Northern European Alps and, therefore, provides a novel technique for the systematic understanding of non-stationary debris flow frequencies in a changing climate.
CRIS-Team WoS Importer:2021-12-10